Tantangan dan Peluang Pelibatan Publik dalam Meningkatkan Mutu Pendidikan di SMAN 13 SURABAYA - qoyyimatus sa'adah, Juwita; Firzatullah Maulana, Rafli; Windasari, Windasari; Hanivia Cindy, Agustin (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2024)
Education management in schools is a series of processes that aim to be effective and efficient in achieving educational goals. Improving the quality of education is an important goal in a country's educational development. One of the key factors in achieving this goal is through public involvement in the education process. Public involvement in improving the quality of education faces challenges such as the community's lack of understanding of their role, constraints on facilities and infrastructure, and limited access to educational information. However, public involvement also provides opportunities for innovation, developing relevant curricula, improving the quality of teaching, and increasing educational accessibility. It is important to overcome these challenges while taking advantage of existing opportunities to develop effective strategies to engage the public in improving the quality of education in Indonesia